The Strengthening of Religious Tolerance through Islamic Education Learning Based on Nonviolence Culture in Public University - Siti Mutholingah (Faculty of Tarbiyah Universitas Islam Tribakti Lirboyo Kediri, 2021)
The public university is an educational institution with heterogeneous and multicultural socio-religious and cultural background conditions for students, including the State University of Malang (UM). The problem that multicultural and multireligious campuses often face is intolerant behavior that allows acts of violence to occur. Nevertheless, interestingly, this does not happen at UM. That is because UM seeks to develop a tolerant attitude of students through Islamic religious education with a culture of non-violence. The aims of this study are: (1) to find out what nonviolence cultural values ​​exist in UM, and (2) what efforts are made by UM to strengthen religious tolerance through Islamic religious education with a culture of nonviolence. This qualitative research applies a case study with data collection techniques through interviews, observation, and documentation. Data analysis includes data collection, condensation, data display, and concluding. The results of this study, namely: (1) The values of the non-violent culture that is being developed by the State University of Malang (UM) are: (a) Rahmatan Lil'alamin values, (b) Peacebuilding values, and (c) Tolerance-values. (2) The strengthening of religious tolerance through non-violent culture through PAI learning at UM includes: (a) The PAI learning process is carried out in the classroom learning directly (2 credits) and in the form of Tafaqquhfiidiinil Islam (TDI) activities which are including public lectures PAI learning and intensive guidance on reading the Qur'an (1 credit) for a total of credit is 3. (b) Through Qur'an Study Club, and (c) Seminar activities on multiculturalism, tolerance, and religious harmony.